Characterization of the Specificity of Imidazoline I-1 Receptor Antibody for Subtype of Imidazoline Receptors In Vitro - Wang, L.-Y.; Ku, P.-M.; Chen, S.-H.; Chen, L.-J.; Yu, Y.-M.; Cheng, J.-T. (Hormone and Metabolic Research, 2013)
Specific antibodies are essential in the study of receptor protein. Gene matching shows that Nischarin (NISCH) is a mouse homologue of human imidazoline receptor antisera-selective (IRAS) protein, a viable candidate for imidazoline I-1 receptor. However, selectivity of this antibody against imidazoline I-2 or imidazoline I-3 receptors remained obscure. At first, an intracerebroventricular (ICV) injection of anti-NISCH antibody blocked the blood pressure lowering action of rilmenidine (I-1 receptor agonist) in spontaneous hypertensive rat (SHR). However, the same injection of anti-NISCH antibody showed no effect in SHR treated with clonidine (α2 agonist). In order to clarify the selectivity of anti-NISCH antibody for each subtype of imidazoline receptors, this anti-NISCH antibody was subjected to the lysate of organs isolated from Wistar rats including cortex, hippocampus, cerebellum, and brain stem as central nervous tissues, and heart, liver, pancreas, skeletal muscle, kidney, prostate, and bladder as peripheral tissues. The results show that anti-NISCH antibody positively reacted with all tissues including heart, pancreas, skeletal muscle, kidney and bladder by Western blot analysis. Also, the blotting spots for anti-NISCH antibody show a concentration-dependent manner. Moreover, anti-NISCH antibody blocked the action of glucose uptake induced by 2-BFI (I-2 receptor agonist) in L6 cells. Taken together, the obtained data suggest that anti-NISCH antibody can be used not only for imidazoline I-1 receptor but also for I-2 and I-3 subtypes in immunoassays.
Keywords: imidazoline I-1 receptor; imidazoline I-2 receptor; imidazoline I-3 receptor; Nischarin (HISCH); imidazoline receptor antisera-selective (IRAS) protein